Pengaruh Faktor Sosial Demografi dan Kinerja Polisi terhadap Kepercayaan Masyarakat kepada Polisi di Indonesia Tahun 2017 - Dina Rahmawati; Rini Silvi (Politeknik Statistika STIS, 2021)
During 2013-2017, the level of public trust in the police continued to increase. Nevertheless, there are still many public complaints about the performance of the police. The police ranked first as the institution complained to Komnas HAM for five years. This indicates that there are other factors beyond police performance that affect public trust in the police. This study aims to determine the socio-demographic and police performance factors that affect public trust in the police in Indonesia and their tendencies. This study analyzed Susenas September 2017 data from BPS using descriptive analysis and inference analysis using binary logistics regression method. The results showed that the area of residence, main activities, gender, age, level of education, economic status, concerns about crime, and involvement with legal institutions have a significant effect on public trust in the police in Indonesia. Police are expected to improve their performance and performance, especially those directly related to the community.